A structure for improving light extraction efficiency of AlGaN-based deep ultraviolet LEDs and its application
By using thin AlGaN layer with gradient Al component content and heavily doped thin p-GaN contact layer in AlGaN-based deep ultraviolet LEDs, the low light extraction efficiency is solved by combining with the Ni/Au/Al electrode structure with high reflectivity. The problem is that efficient light extraction and low operating voltage are achieved.
Patent Information
- Application Number
- CN202210095109.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-01-26
- Publication Date
- 2025-02-25
- Estimated Expiration
- 2042-01-26
AI Technical Summary
The light extraction efficiency of AlGaN-based deep ultraviolet LED is mainly due to the serious absorption of deep ultraviolet light by the p-GaN layer and traditional Ni/Au electrodes, resulting in insufficient light extraction efficiency, which limits the improvement of device performance.
A thin AlGaN layer with gradient Al component content and a heavily doped thin p-GaN contact layer are used to combine with a high reflectivity Ni/Au/Al electrode structure to reduce the absorption of deep ultraviolet light and improve the reflection efficiency of light.
The light extraction efficiency of AlGaN-based deep ultraviolet LED is significantly improved, especially in the range of light emission wavelengths shorter than 300 nm, with a transmittance exceeding 60%, while maintaining good ohmic contact and low operating voltage.
Smart Images

Figure CN114628558B_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of Group III nitride semiconductors, and particularly relates to a device structure and a corresponding electrode structure configuration for improving the light extraction efficiency of an AlGaN-based deep ultraviolet (DUV) light-emitting diode (LED). Background Art
[0002] AlGaN-based deep ultraviolet (wavelength shorter than 300nm) light-emitting diodes (DUV-LEDs) have significant application value in sterilization, water and air purification, and other fields. They are easy to use and do not cause environmental pollution. Therefore, they are highly valued in the public health field and are an irreplaceable solid-state ultraviolet light source.
[0003] However, the current electrical-to-photoelectric conversion efficiency (WPE) of AlGaN-based DUV-LEDs is generally low (less than 10%), posing a major challenge to their industrial-scale application. This is due to factors such as AlGaN crystal quality control, conductivity regulation, active area control, and carrier injection structure, but improving light extraction efficiency remains the primary bottleneck restricting device performance.
[0004] One of the main reasons limiting the light extraction efficiency of DUV-LEDs is that the p-GaN layer and traditional Ni / Au electrodes in DUV-LEDs strongly absorb deep ultraviolet light, resulting in the loss of nearly half of the light emitted from the quantum well, thus seriously affecting the light extraction efficiency.
[0005] To solve this problem, the solution generally adopted internationally is to remove the p-GaN contact layer and use the highly transparent p-AlGaN layer in combination with a high-reflectivity electrode to improve light extraction efficiency, thereby improving the external quantum efficiency. However, the p-AlGaN layer is more difficult to activate holes than the p-GaN layer, resulting in a very low hole carrier concentration; coupled with the large band gap of the AlGaN material, it is impossible to find a metal with a higher work function to form a good ohmic contact with it, which in turn leads to a significant increase in the device operating voltage. The deterioration of the electrical characteristics is very detrimental to the long-term operation of the device.
[0006] Therefore, it is very necessary to develop a device structure and a corresponding p-region electrode structure that can form a good ohmic contact and have high light extraction efficiency in order to realize high-performance AlGaN-based deep ultraviolet LED devices. Summary of the Invention
[0007] In view of the above problems and shortcomings, the present invention proposes an AlGaN-based deep ultraviolet LED device structure with high light extraction efficiency, which has a significant effect on devices with a light emission wavelength shorter than 300nm.
[0008] In a first aspect, the present invention provides an AlGaN-based deep ultraviolet LED device, the structure of which includes: a substrate, and an AlN layer, an AlN / AlGaN layer, an n-AlGaN layer, a quantum well, a p-AlGaN layer, an Al composition gradient AlGaN, and a p-GaN contact layer epitaxially grown on the substrate in sequence; an n-type ohmic contact metal is formed on the n-AlGaN layer; and a p-type ohmic contact metal is formed on the p-GaN contact layer.
[0009] The AlGaN layer has a gradient Al content and a thickness of 5-15 nm.
[0010] The p-GaN contact layer is heavily doped and has a thickness of 2-5 nm;
[0011] The p-type ohmic contact metal is a Ni / Au / Al electrode.
[0012] By employing a thin AlGaN layer with a gradient Al content, a thin heavily doped p-GaN contact layer, and highly reflective Ni / Au / Al electrodes, this new design reduces the absorption of deep UV light by AlGaN-based deep UV LEDs while ensuring good LED surface morphology, good ohmic contact, and low operating voltage. It also reflects most of the light back to the substrate, significantly improving the light extraction efficiency of devices with wavelengths shorter than 300nm. Research results show that the proposed thin-layer design achieves a transmittance of over 60% for 280nm deep UV light, and the thinner the layer, the higher the transmittance, effectively overcoming the low light extraction efficiency of current deep UV LEDs.
[0013] Preferably, the total thickness of the AlGaN layer and the p-GaN contact layer is controlled to be less than 20nm to reduce absorption of ultraviolet light. Further preferably, the thickness of the AlGaN layer is 6-10nm; the thickness of the p-GaN contact layer is 1-5nm.
[0014] Furthermore, in order to effectively overcome the surface deterioration caused by the large lattice mismatch between p-GaN and p-AlGaN and the resulting serious leakage, the Al component content of the AlGaN layer is gradually changed from the Al component content in the p-AlGaN layer to 0; by controlling the gradual decrease of the Al component content, drastic stress release is avoided, thereby maintaining a good surface morphology.
[0015] Preferably, the p-GaN contact layer is heavily doped with Mg, with a doping ratio in the range of 5×10 19 cm -3 -5×10 20 cm -3 , which increases the hole concentration and facilitates the formation of ohmic contact.
[0016] Preferably, the substrate is a sapphire or AlN substrate.
[0017] In a second aspect, the present invention further provides a method for preparing the above-mentioned AlGaN-based deep ultraviolet LED device, comprising:
[0018] 1) On the substrate, epitaxial AlN layer, AlN / AlGaN layer, n-AlGaN layer, quantum well, p-AlGaN layer, AlGaN and p-GaN contact layer are sequentially grown;
[0019] 2) ICP etching to the n-AlGaN layer, evaporating the n-electrode and alloying to form an n-type ohmic contact metal;
[0020] 3) Evaporate a p-electrode on the thin layer of p-GaN, and then evaporate an Al electrode after alloying to form a p-type ohmic contact metal.
[0021] The AlGaN-based deep ultraviolet LED device prepared by the method of the present invention has both high light extraction efficiency and low operating voltage and good electrical performance. At the same time, the method is simple in process and is compatible with traditional LED manufacturing processes, has low cost, can be prepared on a large area, and is suitable for mass production in factories.
[0022] Furthermore, in step 3), the p-electrode is a Ni / Au electrode, and the thickness of the Ni layer and the Au layer are both less than 5 nm to reduce the absorption of ultraviolet light. Preferably, the thickness of the Ni layer is 1-2 nm, and the thickness of the Au layer is 1-2 nm.
[0023] Furthermore, in step 3), the alloying process is performed by annealing at 550°C for 2-10 minutes in an O2 atmosphere. The thickness of the Al electrode is 100-200 nm, preferably 130-180 nm, to ensure reflectivity for deep ultraviolet light. The Ni / Au / Al electrode achieves good ohmic contact with the p-GaN contact layer and efficiently reflects deep ultraviolet light to the sapphire substrate.
[0024] Furthermore, in step 2), the n-electrode is one or a combination of titanium, aluminum, nickel, gold, chromium, vanadium, etc., or an alloy thereof, and the alloying process is to anneal the metal electrode in a nitrogen atmosphere at 600-1000° C. for 20-60 seconds.
[0025] In a third aspect, the present invention further provides applications of the above-mentioned AlGaN-based deep ultraviolet LED device in the fields of sterilization, disinfection, water and air purification, etc.
[0026] The beneficial effects of the present invention are as follows:
[0027] 1. The present invention reduces the thickness of the thin AlGaN layer with a gradient composition and the p-GaN contact layer and matches the thickness relationship, which is beneficial to the stable control of the structure and the guarantee of electrical properties, while reducing the absorption of deep ultraviolet light and significantly improving the light extraction efficiency.
[0028] 2. Compared with traditional electrodes, the Ni / Au / Al electrode used in the present invention has a higher reflectivity in the deep ultraviolet band and can also form a good ohmic contact with the p-GaN contact layer to ensure a low operating voltage.
[0029] 3. The deep ultraviolet LED preparation method adopted in the present invention has a simple process, is easy to repeat, has low cost, can be prepared on a large area, and is suitable for mass production in factories. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a schematic structural diagram of a deep ultraviolet LED structure with high light extraction efficiency provided in Example 1.
[0031] In the figure: 1 is the substrate; 2 is the AlN layer; 3 is the AlN / AlGaN multi-period modulation layer; 4 is the n-AlGaN layer; 5 is the multi-quantum well layer; 6 is the p-AlGaN (including EBL) layer; 7 is the thin AlGaN transition layer with a gradient Al composition and the p-GaN contact layer; 8 is the n-type ohmic contact metal; 9 is the p-type ohmic contact metal.
[0032] Figure 2 Schematic diagram of the structure of the p-type electrode obtained in Example 1; in the figure: 10 is Ni, 11 is Au, and 12 is Al.
[0033] Figure 3 is a TLM graph, where L is the side length of the electrode, d1, d2, d3, d4, d5, d6, and d7 are the distances between two adjacent electrodes, and E1, E2, E3, E4, E5, E6, E7, and E8 refer to the electrodes respectively.
[0034] Figure 4 It is the IV curve between adjacent electrodes in the TLM graph.
[0035] Figure 5 Comparison of LED epitaxial wafer surfaces with (a) and without (b) AlGaN graded transition layer (10x optical microscope). DETAILED DESCRIPTION
[0036] The following examples are used to illustrate the present invention but are not intended to limit the scope of the present invention.
[0037] Example 1
[0038] The present invention provides a deep ultraviolet LED with good ohmic contact and high light extraction efficiency, the structure of which is as follows: Figure 1As shown, the following steps are included:
[0039] 1) On the surface of substrate 1, an AlN layer 2, an AlN / AlGaN multi-period modulation layer 3, an n-AlGaN layer 4, a multi-quantum well layer 5, a p-AlGaN (including EBL) layer 6, a thin AlGaN transition layer with a gradient Al composition, and a p-GaN contact layer 7 are sequentially epitaxially grown by MOCVD.
[0040] 2) Using photolithography and ICP etching techniques, the unprotected n-type region is etched by about 400 nm to expose the surface of the n-AlGaN layer;
[0041] 3) Prepare n-type ohmic contact metal 8 on the surface of n-AlGaN 4 by electron beam evaporation and rapidly anneal in N2 atmosphere at 850℃ for 35s;
[0042] 4) Forming a p-type ohmic contact metal Ni / Au on the surface of the p-GaN contact layer 7 by electron beam evaporation, and rapidly annealing in an O2 atmosphere at 550°C for 300s, followed by evaporation of an Al metal combination to form a p-type ohmic contact metal 9;
[0043] Figure 2 Schematic diagram of the structure of the p-type electrode; in the figure, 10 is Ni, 11 is Au, and 12 is Al.
[0044] Verification of electrical properties of new electrodes
[0045] 1. The verification method is as follows:
[0046] (1) Epitaxially grow a 1 μm thick AlN buffer layer on a sapphire substrate;
[0047] (2) Epitaxial unintentionally doped u-GaN with a thickness of 2 μm;
[0048] (3) Epitaxial growth of a 200 nm thick p-GaN layer;
[0049] (4) Photolithography forms a TLM pattern on the p-GaN layer, where the pattern of the photolithography plate used is as follows: Figure 3 As shown, the electrode side length L = 200 μm, and the distance dn between two adjacent electrodes is 10, 15, 20, 25, 30, 35, and 40 μm respectively;
[0050] (5) Forming a 2 nm Ni layer and a 1 nm Au layer on the surface of the p-GaN layer by electron beam evaporation;
[0051] (6) After metal stripping, the sample was rapidly annealed in an O2 atmosphere at 550 °C for 5 min;
[0052] (7) A 150 nm Al metal layer was formed on the surface of the Au layer by electron beam evaporation to form a Ni / Au / Al electrode.
[0053] 2. Effect verification
[0054] Measurement Figure 3 The IV curve of each adjacent two electrodes is plotted as follows: Figure 4 As shown, the specific contact resistivity of the Ni / Au / Al electrode is obtained by fitting the data to ρ c =1.5×10 -3 (Ω·cm 2 ), indicating that the electrical properties of the Ni / Au / Al electrode are good.
[0055] In addition, by directly preparing the Ni / Au / Al electrode on a double-polished sapphire substrate, the reflectivity spectrum test showed that its ultraviolet light reflectivity was higher than 60%.
[0056] The above experimental results show that when the electrode is applied to the device, it can ensure good electrical properties while efficiently reflecting ultraviolet light to the substrate side, greatly increasing the light extraction efficiency.
[0057] Example 2
[0058] This embodiment provides a method for preparing a deep ultraviolet LED with high light extraction efficiency, comprising:
[0059] 1) 2μm AlN layer 2 was epitaxially grown on the (0001) sapphire substrate using MOCVD method; AlN / Al 0.55 Ga 0.45 N stress buffer layer 3; 2μm n-Al 0.55 Ga 0.45 N layer 4; 5 pairs of Al 0.35 Ga 0.65 N / A 0.65 Ga 0.35 N quantum well layer 5; 25nm p-Al 0.75 Ga 0.25 N EBL layer 6; 9nm AlGaN transition layer with Al composition rapidly changing from 0.75 to 0 and 3nm p-GaN heavily doped contact layer 7;
[0060] 2) Using photolithography and ICP etching technology, the unprotected n-type area is etched about 400nm to expose the n-Al 0.55 Ga 0.45 N-layer surface;
[0061] 3) Prepare n-type ohmic contact metal 8 by electron beam evaporation and rapidly anneal in N2 atmosphere at 850°C for 35s;
[0062] 4) A p-type ohmic contact metal Ni / Au (2nm-Ni / 2nm-Au electrode) is fabricated on the surface of the p-GaN thin layer by electron beam evaporation, followed by rapid annealing in an O2 atmosphere at 550°C, followed by vapor deposition of Al metal to form a p-type ohmic contact metal 9.
[0063] Comparative Example 1
[0064] Comparative Example 1 is a conventional LED structure and p-region electrode structure, and the specific preparation steps are as follows:
[0065] 1) 2μm AlN layer 2 was epitaxially grown on the (0001) sapphire substrate using MOCVD method; AlN / Al 0.55 Ga 0.45 N stress buffer layer 3; 2μm n-Al 0.55 Ga 0.45 N layer 4; 5 pairs of Al 0.35 Ga 0.65 N / A 0.65 Ga 0.35 N quantum well layer 5; 25nm p-Al 0.75 Ga 0.25 N EBL layer 6; 20nm p-Al 0.5 Ga 0.5 N6; 20nm p-GaN contact layer 7;
[0066] The difference from Example 2 is that the 7 layers are different, specifically the thickness of the AlGaN and p-GaN contact layers are thicker, and the Al component content of the AlGaN layer remains unchanged;
[0067] 2) Using photolithography and ICP etching technology, the unprotected n-type area is etched about 400nm to expose the n-Al 0.55 Ga 0.45 N-layer surface;
[0068] 3) Prepare n-type ohmic contact metal 8 by electron beam evaporation and rapidly anneal in N2 atmosphere at 850°C for 35s;
[0069] 4) Fabricate p-type ohmic contact metal (5nm-Ni / 10nm-Au electrodes) on the surface of the p-GaN thin layer by electron beam evaporation and rapidly anneal in an O2 atmosphere at 550°C;
[0070] The difference from Example 2 is that no Al metal is further evaporated, the electrode is a Ni / Au electrode, and the electrode layer is thicker.
[0071] Effect verification
[0072] The LED device obtained in Example 2 and the LED device obtained in Comparative Example 1 were tested at a light emission wavelength of 278 nm. The results are as follows:
[0073] The voltage of the 2nm-Ni / 2nm-Au electrode of the LED device obtained in Example 2 is 6.5V at an operating current of 100 mA, which is equivalent to the ~6.4V of the 5nm-Ni / 10nm-Au electrode of the LED device obtained in Comparative Example 1. At the same time, at an operating current of 100 mA, the external quantum efficiency of the LED device obtained in Comparative Example 1 is only 3.87%, while the external quantum efficiency of the LED device obtained in Example 2 reaches 6%, an increase of 55%, which greatly improves the device performance.
[0074] Example 3
[0075] This example verifies the role of the AlGaN graded transition layer (to enhance the comparison effect, the p-GaN thickness is 10 nanometers). The specific structure includes:
[0076] 1) 2μm AlN layer 2 was epitaxially grown on the (0001) sapphire substrate using MOCVD method; AlN / Al 0.55 Ga 0.45 N stress buffer layer 3; 2μm n-Al 0.55 Ga 0.45 N layer 4; 5 pairs of Al 0.35 Ga 0.65 N / A 0.65 Ga 0.35 N quantum well layer 5; 25nm p-Al 0.75 Ga 0.25 N EBL layer 6; 9 nm AlGaN transition layer with Al composition rapidly changing from 0.75 to 0; and 10 nm p-GaN contact layer 7;
[0077] Comparative Example 2
[0078] The epitaxial structure of Comparative Example 2 is different from that of the embodiment, but without the AlGaN graded transition layer. The specific structure is as follows:
[0079] 1) 2μm AlN layer 2 was epitaxially grown on the (0001) sapphire substrate using MOCVD method; AlN / Al 0.55 Ga 0.45 N stress buffer layer 3; 2μm n-Al 0.55 Ga 0.45 N layer 4; 5 pairs of Al 0.35 Ga 0.65 N / A 0.65 Ga 0.35 N quantum well layer 5; 25nm p-Al 0.75 Ga 0.25N EBL layer 6; 10nm p-GaN contact layer 7;
[0080] The difference from Example 3 is that the graded p-AlGaN transition layer is not used.
[0081] Effect verification
[0082] Compare the LED epitaxial wafer structure surfaces of Example 3 and Comparative Example 2. Figure 5 As shown, the results are as follows:
[0083] Under a 10x optical microscope, the surface of the LED epitaxial wafer obtained in Example 3 was bright and had an excellent surface condition that met the requirements for device manufacturing; while the surface of Comparative Example 2 had many pit-like structures, which seriously restricted further device preparation.
[0084] Although the present invention has been described in detail above using general descriptions and specific embodiments, it will be apparent to those skilled in the art that modifications and improvements may be made based on the present invention. Therefore, such modifications and improvements, which do not depart from the spirit of the present invention, are intended to be within the scope of protection claimed herein.
Claims
1. An AlGaN-based deep ultraviolet LED device, characterized in that: The structure includes: A substrate, and an AlN layer, an AlN / AlGaN layer, an n-AlGaN layer, a quantum well, a p-AlGaN layer, an Al composition gradient AlGaN layer and a p-GaN contact layer epitaxially grown in sequence on the substrate; forming an n-type ohmic contact metal on the n-AlGaN layer; forming a p-type ohmic contact metal on the p-GaN contact layer; The Al component content of the Al component gradient AlGaN layer gradually changes from the Al component content in the p-AlGaN layer to 0, and the thickness thereof is 6-10 nm; The p-GaN contact layer is heavily doped and has a thickness of 2-5 nm; The p-type ohmic contact metal is a Ni / Au / Al electrode; The total thickness of the Al composition gradient AlGaN layer and the p-GaN contact layer is controlled to be less than 20 nm.
2. The AlGaN-based deep ultraviolet LED device according to claim 1, characterized in that: The thickness of the p-GaN contact layer is 1-5 nm.
3. The method for preparing the AlGaN-based deep ultraviolet LED device according to claim 1 or 2, characterized in that: include: 1) On the substrate, epitaxially grow an AlN layer, an AlN / AlGaN layer, an n-AlGaN layer, a quantum well, a p-AlGaN layer, an Al composition gradient AlGaN layer and a p-GaN contact layer in sequence; 2) ICP etching to the n-AlGaN layer, evaporating the n-electrode and alloying to form an n-type ohmic contact metal; 3) Evaporate a p-electrode on the thin layer of p-GaN, and then evaporate an Al electrode after alloying to form a p-type ohmic contact metal.
4. The preparation method according to claim 3, characterized in that: In step 3), the p-electrode is a Ni / Au electrode, and the thickness of the Ni layer and the Au layer are both less than 5 nm.
5. The preparation method according to claim 4, characterized in that: The thickness of the Ni layer is 1-2 nm, and the thickness of the Au layer is 1-2 nm.
6. The preparation method according to claim 3, characterized in that: The thickness of the Al electrode is 100-200 nm.
7. The preparation method according to claim 6, characterized in that: The thickness of the Al electrode is 130-180 nm.
8. The preparation method according to claim 3, characterized in that: In step 2), the n-electrode is one or a combination of titanium, aluminum, nickel, gold, chromium, vanadium or an alloy thereof; the alloying process is annealing the metal in a nitrogen atmosphere at 600-1000° C. for 20-60 seconds.
9. Application of the AlGaN-based deep ultraviolet LED device according to claim 1 or 2 in the fields of sterilization, water and air purification.
Citation Information
Patent Citations
Ultraviolet light-emitting diode with high reflection film and manufacturing method of ultraviolet light-emitting diode
CN103165775A
Method for improving light extraction efficiency of TM mode of ultraviolet AlInGaN light emitting diode
CN112713227A
Deep ultraviolet LED with ultrathin p-AlGaN structure
CN212542463U